Acute and cumulative effects of carboplatin on renal function. - Sleijfer, D. T. (Nature Publishing Group, 1989)
Carboplatin, a cisplatinum analogue, has no reported nephrotoxicity in phase I/II studies, assessed by creatinine clearance. We prospectively determined renal function in 10 untreated lung cancer patients with normal baseline renal function, treated with carboplatin 400 mg m-2 day 1 and vincristine 2 mg day 1 and 8 every 4 weeks (max. five cycles) by means of clearance studies with 125I-sodium thalamate and 131I-hippurate to determine GFR and ERPF respectively. Tubular damage was monitored by excretion of tubular enzymes and relative beta 2-microglobulin clearance. During the first course no changes in renal function were seen. After the second course a significant fall in GFR and ERPF started, ultimately leading to a median decrease in GFR of 19.0% (range 6.8-38.7%) and in ERPF of 14% (range 0-38.9%). No increases in the excretion of tubular enzymes or changes in the relative beta 2-microglobulin clearances were seen. We conclude from our data that carboplatin causes considerable loss of renal function. Monitoring renal function in patients treated with multiple courses of carboplatin is warranted.